The Influence of Tax Sanctions, Tax Services, and Tax Understanding on Individual Taxpayer Compliance at the West Medan Pratama KPP - Situmorang, Evlyn; Siahaan, Septony; Simanjuntak, Gracesiela (Future Science, 2025)
Taxes are the main source of state revenue used to finance infrastructure development and non-physical sectors. However, taxpayer compliance remains a significant challenge, especially in Indonesia. This study aims to analyze the impact of tax sanctions, tax services, and tax understanding on the compliance of individual taxpayers at KPP Pratama Medan Barat. Data were obtained from 54 respondents through questionnaires and analyzed using multiple linear regression with the help of SPSS version 26. The research results show that tax sanctions do not have a significant impact, whereas service and tax understanding have a positive and significant impact on the level of compliance. These findings can be used as input for policies to improve tax compliance.